The knowledge that went up in smoke: Reindeer herders' traditional knowledge of smoked reindeer meat in literature - Hansen, Kia Krarup; Moldenæs, Turid; Mathiesen, Svein Disch (Polar Record, 2020)
Using a literature review, this paper defines the knowledge status of smoked reindeer meat and investigates to what degree reindeer herders’ traditional knowledge has been included in scientific articles and grey literature. We developed a four-level categorisation of the degree of including traditional knowledge, from “non-participation” to “self-determination,” and three levels of focus. Very few scientific articles on smoked or smoking reindeer meat appeared in the review. Not only did reindeer peoples’ traditional meat smoking knowledge “went up in smoke”—both literally and metaphorically—but also incorrect conclusions were often drawn as a result of that exclusion. We argue that reindeer herders’ traditional knowledges and practices of smoking reindeer meat need examination and inclusion through co-production or self-determination methods across scientific disciplines.